Recent advances in the rehabilitation of anterior cruciate ligament injuries - Wilk, K. E.; Macrina, L. C.; Cain, E. L.; Dugas, J. R.; Andrews, J. R. (Journal of Orthopaedic & Sports Physical Therapy, 2012)
Rehabilitation following anterior cruciate ligament surgery continues to change, with the current emphasis being on immediate weight bearing and range of motion, and progressive muscular strengthening, proprioception, dynamic stability, and neuromuscular control drills. The rehabilitation program should be based on scientific and clinical research and focus on specific drills and exercises designed to return the patient to the desired functional goals. The goal is to return the patient`s knee to homeostasis and the patient to his or her sport or activity as safely as possible. Unique rehabilitation techniques and special considerations for the female athlete will also be discussed. The purpose of this article is to provide the reader with a thorough scientific basis for anterior cruciate ligament rehabilitation based on graft selection, patient population, and concomitant injuries.